PENERAPAN PARIWISATA BERKELANJUTAN SEBAGAI UPAYA PENGEMBANGAN DESA WISATA (Studi Kasus Desa Wisata Lerep) - Florensia Marveina; Samtono Samtono; Yustina Denik (JURNAL ILMIAH EDUNOMIKA, 2023)
The tourism sector has a significant role in the country's development, such as reducing unemployment and adding new jobs. The tourism sector has a significant role in the country's development, such as reducing unemployment and adding new jobs. Lerep Tourism Village offers a wide choice of tourist destinations thanks to its supporting natural scenery. Lerep tourist village with sustainable tourism theory which pays attention to environmental, cultural and economic aspects. Tourism activities in Lerep Tourism Village have an impact on environmental factors which can be seen from indicators including organized waste management. Tourism activities in the Lerep Tourism Village have an impact on cultural sustainability as seen from the values of local wisdom which are still firmly held by the community and visitors are also involved in maintaining local wisdom. Tourism activities in Lerep Tourism Village have an impact on economic factors, namely the emergence of new job opportunities for the community Keywords: Tourism Village, Sustainable Tourism